Diamidophosphites from β-hydroxyamides: readily assembled ligands for Pd-catalyzed asymmetric allylic substitution. Issue 17 (14th April 2020) - Chuchelkin, Ilya V.; Gavrilov, Konstantin N.; Borisova, Nataliya E.; Perepukhov, Alexander M.; Maximychev, Alexander V.; Zheglov, Sergey V.; Gavrilov, Vladislav K.; Firsin, Ilya D.; Zimarev, Vladislav S.; Mikhel, Igor S.; Tafeenko, Victor A.; Murashova, Elena V.; et al.
Abstract : Novel diamidophosphites based on β-hydroxyamides were prepared, and their individual and in situ formed complexes were tested in Pd-mediated allylations. Abstract : Two groups of modular chiral diamidophosphite ligands were easily synthesised from accessible N -Boc-amino alcohols and pseudodipeptides. The reaction of these compounds with [Pd(allyl)Cl]2 in the presence of AgBF4 yielded complexes [Pd(allyl)(L)2 ]BF4 . In addition, metallochelates [Pd(allyl)(L)]BF4 with ( S )-methioninol-based P, S -bidentate ligands were prepared. The structures of the novel ligands and complexes were elucidated by means of 2D-NMR and were confirmed by single-crystal X-ray diffraction, as well as by DFT calculations. Asymmetric inducers of this type exhibited high enantioselectivities in the Pd-mediated allylic substitution of ( E )-1, 3-diphenylallyl ethyl carbonate with CH2 (CO2 Me)2 (up to 98% ee) and (CH2 )4 NH (up to 92% ee). Ee values of up to 86% and 73% were obtained in the Pd-catalyzed allylic alkylation of cinnamyl acetate with ethyl 2-oxocyclohexane-1-carboxylate and ethyl 2-oxocyclopentane-1-carboxylate, respectively. The effects of the structural modules, such as the nature of the phosphorus-containing ring or exocyclic substituent, on the catalytic activity and enantioselectivity were investigated.